Water quality index development for groundwater quality assessment of Greater Noida sub-basin, Uttar Pradesh, India. Issue 1 (31st December 2016) - Singh, Sajal; Hussian, Athar
Abstract: The water quality index (WQI) is an important parameter for determining the drinking water quality for the end users. The study for the same has been carried on the groundwater by collecting 47 groundwater samples from 25 blocks of Greater Noida city, India. In order to develop WQI the samples were subjected to a comprehensive physicochemical and biological analysis of 11 parameters such as pH, calcium, magnesium, chloride, nitrate, sulphate, total dissolved solids, fluorides, bicarbonate, sodium and potassium. Geographical information system has been used to map the sampling area. The coordinates in terms of latitude and longitude of the sampling locations were recorded with the help of global positioning system. Piper plots and cation–anion correlation matrix were plotted from the values obtained by the analysis of various parameters. The WQI index for the same has been calculated and the values ranged from 53.69 to 267.85. The WQI values from present study indicate the very poor quality water in the area dominated by industrial and construction activities. Poor water quality has been observed in commercial zone of the study area. The analysis reveals the fact that the ground water of the Greater Noida needs a degree of treatment before consumption and needs to be protected from further contamination.